2022
DOI: 10.1021/acs.jafc.2c01100
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Oxidized Soybean Oil Administration in Rats during Pregnancy and Lactation Alters the Intestinal DNA Methylation in Offspring

Abstract: As a food contaminant, oxidized oil or lipid oxidative products have been proven to exert toxicological effects on the growth and development of animals and humans. Research shows that maternal oxidative stress damage might transmit to another generation by epigenetic modulation. However, current evidence is still not clear on the mechanism of the effects of dietary oxidized oil during pregnancy on the two generations. This study employed a rat model fed with oxidized soybean oil (OSO) during pregnancy and lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Previously, our study showed that maternal exposure to OSO resulted in damage to the placenta and offspring intestinal. , However, very few studies have evaluated the effect of OSO on the liver metabolism of fatty acids in maternal and their offspring. In the liver, oxidized lipids accumulate at the highest level .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, our study showed that maternal exposure to OSO resulted in damage to the placenta and offspring intestinal. , However, very few studies have evaluated the effect of OSO on the liver metabolism of fatty acids in maternal and their offspring. In the liver, oxidized lipids accumulate at the highest level .…”
Section: Discussionmentioning
confidence: 99%
“…POV was examined in previous research. 20 Experimental Animals and Designs. A total of sixty female Sprague−Dawley (SD) rats were purchased from Liaoning Changsheng Biotechnology Co., Ltd (Shenyang, China), with the animal permit number SCXK (Liao) 2015-0001.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mRNA expression levels of Mettl3 , Mettl14, Alkbh5 and Fto are decreased in placentas after OSO ingestion, with a lower global m 6 A level. The placental genes with differential m 6 A levels are related to nutrient metabolic process and hormone activity ( Wang et al, 2022b ). In addition, exposure to BPDE [benzo(a)pyrene-7,8-dihydrodiol-9,10-epoxide], the metabolite of Benzo(a)pyrene (BaP) which is one representative of PAHs (polycyclic aromatic hydrocarbons), upregulates the expression level of m 6 A-modified lnc-HZ01 and inhibits the proliferation of trophoblast cells.…”
Section: Rna M 6 a Act As Sensitive Effectors And ...mentioning
confidence: 99%
“…Epigenetics is a possible link between the environment and fetal growth, and RNA m 6 A is also inherited across generations. Maternal ingestion of oxidized soybean oil (OSO) during gestation and lactation disturbs the homeostasis of DNA/RNA methylation and negatively affects the placental function and intestinal development in offspring, with a reduced height of villi and a lower level of anti-inflammatory factors ( Wang et al, 2022b ). In addition, maternal engineered nanomaterial (ENM) exposure increases the m 6 A level in the 3′UTR region of mitochondria phospholipid hydroperoxide glutathione peroxidase (mPHGPx) which is an antioxidant enzyme that protects fetal cells from oxidative stress.…”
Section: Rna M 6 a Act As Sensitive Effectors And ...mentioning
confidence: 99%